Penerapan Labelisasi Halal Dan Digital Marketing Untuk Meningkatkan Minat Beli Konsumen Madu - Mundir, Abdillah; Khoifah, Siti (STAI Denpasar Bali, 2023)
The halal label is part of the product with product information the packaging. Companies must apply halal labeling on packaging because to provide certainty about the halal status of these products give confidence to Muslim consumers. Digital marketing form of business that carries out marketing and advertising of brands products throughout the digital world. the application of digital marketing through social media used companies can increase revenue and attract consumers. Honey picking tours have implemented halal labeling and digital marketing for honey products.The purpose of this research first to find out application of halal labeling to consumer buying interest and the second goal is find out application of halal labeling to consumer buying interest in picking honey tours. This type of research used qualitative research using a descriptive approach. research instruments used by researchers in this research observation, interviews, and documentation. From the results of the study was found the application of halal labeling in honey picking tours includes process for obtaining halal labeling on packaging. application of digital marketing to consumer buying interest using E-commerce. existence of digital marketing very large positive impact on companies, including increasing sub-sales, saving promotional power, facilitating communication between companies and consumers.